2009
DOI: 10.1057/jors.2008.130
|View full text |Cite
|
Sign up to set email alerts
|

Credit scoring with macroeconomic variables using survival analysis

Abstract: Survival analysis can be applied to build models for time to default on debt. In this paper we report an application of survival analysis to model default on a large data set of credit card accounts. We explore the hypothesis that probability of default is affected by general conditions in the economy over time. These macroeconomic variables cannot readily be included in logistic regression models. However, survival analysis provides a framework for their inclusion as time-varying covariates. Various macroecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(116 citation statements)
references
References 20 publications
5
106
0
5
Order By: Relevance
“…the strong do not become stronger. In fact in our experiment the performance of the best performing two-class classifier, logistic regression, registered a small decline when oversampling was applied which matches the results of Bellotti and Crook (2009). Based on these findings, oversampling should not be employed with logistic regression as a suitable technique to address the LDP problem.…”
Section: Discussionsupporting
confidence: 74%
“…the strong do not become stronger. In fact in our experiment the performance of the best performing two-class classifier, logistic regression, registered a small decline when oversampling was applied which matches the results of Bellotti and Crook (2009). Based on these findings, oversampling should not be employed with logistic regression as a suitable technique to address the LDP problem.…”
Section: Discussionsupporting
confidence: 74%
“…The Cox proportional hazards model was also used for bankruptcy prediction in Duffie et al [31]. T. Bellotti and J. Crook [32]) in their research reported an application of survival analysis to model default on a large data set of credit card accounts.…”
Section: Guptamentioning
confidence: 99%
“…For further details about building and assessment of a survival model using application and macroeconomic variables for retail credit cards, see Bellotti and Crook (2009). Models were built with behavioural variables lagged by 12 months in order to reduce the possible effect of endogeneity between behavioural data and default event (eg a rise in account balance and default may have a common external cause) and to allow for forecasts up to 12 months ahead.…”
Section: Model Fitmentioning
confidence: 99%
“…Rösch and Scheule (2008) present a general stress testing approach based on an asset correlation model that includes macroeconomic factors and show it can be used to estimate stressed loss rates, given severe economic scenarios. Bellotti and Crook (2009) …”
Section: Introductionmentioning
confidence: 99%